The effect of physically or non-physically forced sexual assault on trajectories of sport participation from adolescence through young adulthood - Chung Gun Lee; Junhye Kwon; Hojun Sung; Inae Oh; Ohsup Kim; Jeehyun Kang; Ji-Won Park (BMC, 2020)
Abstract Background Sexual assault is one of potential factors that may greatly affect an individual's sport participation. The purpose of this study is to investigate the effect of experiencing physically or non-physically forced sexual activity on trajectories of sport participation from adolescence to young adulthood. Methods This study used the National Longitudinal Study of Adolescent Health (Add Health) data. Group-based trajectory modeling was utilized to examine the effect of experiencing sexual assault on trajectories of sport participation from adolescence to young adulthood. Results A three-group trajectory model (high-stable group, high-decreasing group, and low-stable group) best fit sport participation among male participants and a two-group trajectory model (high-decreasing group and low-stable group) best fit sport participation among female participants. Both physically and non-physically forced sexual activity did not have significant effect on trajectories of sport participation among male participants. On the other hand, non-physically forced sexual assault significantly affected sport participation trajectory among female participants. Conclusions Special care is required in developing sport promotion program for women victims of non-physically forced sexual activity. The results of this study also suggest that group-based trajectory modeling is a useful technique to examine distinct trajectories of sport participation from adolescence through young adulthood.